South-south trade in global development - Parsan, Elizabeth (Avebury, 1993)
This study aims to provide a comprehensive evaluation of the major issues involved in a strategy of South-South trade, and demonstrates the actual potential and problems of such trade through a case study of Brazil-Trinidad and Tobago trade in the petrochemicals sector